Disain Peningkatan Penjualan Produk Dengan Pendekatan Kano Dan Quality Function Deployment (QFD) - Erawati, Andri; Lukmandono, Lukmandono; Prabowo, Rony (Institut Teknologi Adhi Tama Surabaya, 2020)
The exhibition that has been followed by the SMEs in East Java is currently profitable and hurt. The advantage of the exhibition is the SMEs helped to introduce the product, but still less profitable for the SMEs because not all the exhibits crowded by consumers, so it is not optimal in the sale of products. It is influenced by several things such as location selection, less weighted exhibit themes and many other things that can affect. This research aims to determine the attributes of consumers ' desire to increase product sales along with a prioritized technical function variable to be repaired through the integration of the Kano method and the Quality Function Deployment. From the calculations obtained category Must be 5 attributes, One Dimensional 3 attribute, attractive 5 attributes and Indeffrent 2 attributes. Where is the value of Adjustment Importance (%) of the highest value is as follows: promotion and publication of exhibitions by Event Organizer is more driven/active in digital media as well as newspapers to attract 11.77% of visitors, selection of the right area according to the products offered and local community shots 11.38%, decoration exhibition stand more impressive 11.18%, and security and cleanliness during maintenance maximum 11.08%.